Building something better : environmental crises and the promise of community change - Malin, Stephanie A., 1981-; Kallman, Meghan Elizabeth (Nature, society, and culture., 2022)
"As the turmoil of interlinked crises unfold across the nation and world -- crises ranging from climate disasters to the rise of authoritarianism to state-sponsored violence -- social scientists can explain what is happening and why. Malin and Kallman offer an accessible, clear book, showing how communities are building better systems and how sociology can help us understand how and why they do this challenging work. Tackling neoliberalism head-on, these communities engage the structures that led us here and show how communities counter the structural violence of neoliberalism by building more distributive and regenerative systems. Malin and Kallman begin by analyzing the origins of these unprecedented social and environmental crises -- critiquing structures from colonialism to the state to extractivism. They dig into sociology's colonial past and the consequences of it, arguing that environmental sociology still has the tools to become a more inclusive and intersectional social science. They examine the origins and staying power of neoliberal ideologies, policies, and culture -- and show why they create such persistent problems. The authors then present an array of case studies, exploring how community-centered efforts expand beyond neoliberal capitalism's limitations. They show how communities craft more distributive and regenerative systems that fundamentally depart from neoliberal capitalism. These communities range from regenerative hemp farmers, to water protectors to activists fighting oil refineries and uranium mines, to celebratory street band musicians, and Indigenous-led renewable energy cooperatives. All are examples of communities creating new approaches to counter crises like inequality, climate catastrophe, and alienation. These illustrations are emergent, happening in real time and on-the-ground, and are visionary departures from business-as-usual models, showing how people can transform social inequality and environmental injustice"--